RANCANG BANGUN OVEN PENGASAPAN IKAN DENGAN MENGOPTIMALKAN SEBARAN PANAS - Pardi, Pardi; Septi Ayu A; Nur Audina (ABEC Indonesia, 2023)
One of the marine resources that needs to be developed is fish. In certain seasons the catch of fishermen is very abundant. Therefore it is necessary to have technology in processing fish caught by fishermen or cultivated fish. In this study, a fish processing tool was created by smoking. In smoking fish so that it is fit for consumption, it must comply with applicable standards, one of which is the Indonesian National Standard (SNI). The smoked fish oven has a length of 85 cm, a width of 45 cm and a height of 140 cm using stainless steel material. The process of making the oven is carried out using a shielded metal arc welding process using the added material E 316. The smoked fish oven is made using skilled personnel and supervision is carried out starting from reading drawings, marking on the material, cutting and assembling processes. Deformation handling is very necessary in the welding process to get a good construction shape.